Comparison of Oversized Artery and Vein Grafts for Interpositional Pedicle Lengthening in Rat Femoral Artery - Simsek, Tekin; Demir, Ahmet; Engin, Murat Sinan; Yildiz, Levent; Kelahmetoglu, Osman; Bek, Yuksel; Bayrak, Ilkay Koray (Journal of Reconstructive Microsurgery, 2014)
Vessel grafting is commonly used for revascularization or pedicle lengthening. Although veins are more commonly used, they can form aneurysms when bridging an arterial gap. This can lead to thrombosis, and the risk is increased when there is a size discrepancy. This study reports the long-term results of arterial lengthening via size discrepant carotid artery and femoral vein grafts in a rat femoral artery model (1:1.5 ratio). A total of 28 rats were used in this study, divided into two groups of 14. By the 21st day, one anastomosis in each group has been found to be thrombosed. Long-term patency rates were the same for both groups (93.3%). Radiologic imaging showed that size match in the carotid artery grafts was excellent despite of slightly fusiform dilatation, but in the vein groups, pronounced aneurismal deformation and distortion in the anastomosis was seen. Histologic analysis revealed that in the arterial grafts, endothelial continuity was smooth and mural inflammation was less than that of the vein grafts. Organized or recanalized mural thrombi were seen in 38.5% in the vein grafts, whereas in arterial grafts there were none.
Keywords: microvascular grafting; pedicle lengthening; size discrepancy